DEVELOPMENT OF CONTEXTUAL STUDENT WORKSHEETS BASED ON THE JAMBI ENVIRONMENT TO ENHANCE NUMERACY - Aisyah Aisyah; Dadang Juandi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Challenges in students’ numeracy skills remain a persistent issue in mathematics classrooms in Indonesia, particularly when teaching materials are not connected to students’ real-life contexts. Addressing this gap, the present study aims to develop aÂ Student WorksheetÂ designed based on theÂ local environmental context of JambiÂ within theÂ Education for Sustainable Development (ESD)Â perspective on number topics to enhance students’ numeracy achievement. This study employs theÂ Plomp development model, which consists of three phases: preliminary investigation, design and realization, and evaluation. Data were collected through expert validation sheets, interviews, and numeracy literacy tests. The results of expert assessments indicate that the developed product is highly feasible in terms of content, language, and design. Field testing conducted in Class VII A of SMP N 11 Kota Jambi showed that the average numeracy test score of 34 students reachedÂ 80.47, exceeding theÂ Minimum Mastery Criterion (75). These findings indicate that the contextual-based Student Worksheet is effective in improving students’ numeracy and in strengthening their connection to local contexts as a means of fostering sustainability awareness.Tantangan dalam keterampilan numerasi murid masih menjadi persoalan yang terus berlanjut di kelas-kelas matematika di Indonesia, terutama ketika bahan ajar tidak terhubung dengan konteks kehidupan nyata murid. Menjawab kesenjangan tersebut, penelitian ini bertujuan untuk mengembangkan Lembar Kerja Murid (LKM) yang dirancang berdasarkan kontekstual lingkungan lokal Jambi dalam perspektif Education for Sustainable Development (ESD) pada materi bilangan untuk meningkatkan pencapaian numerasi murid. Penelitian ini menggunakan model pengembangan Plomp yang terdiri atas tiga fase, yaitu investigasi awal, perancangan dan realisasi, serta evaluasi. Pengumpulan data dilakukan melalui lembar validasi ahli, wawancara, dan tes literasi numerasi. Hasil penilaian para ahli menunjukkan bahwa produk tersebut sangat layak ditinjau dari aspek materi, bahasa, dan desain. Uji coba lapangan di kelas VII A SMP N 11 Kota Jambi, menunjukkan hasil rata-rata tes numerasi 34 murid sebesar 80,47 yang melampaui Kriteria Ketuntasan Minimun (75). Temuan ini mengindikasikan bahwa LKM berbasis kontekstual efektif dalam meningkatkan numerasi serta memperkuat keterhubungan murid dengan konteks lokal untuk menanamkan kesadaran keberlanjutan.